Participation of muslim in the leisure and recreational activities in Kuching, Sarawak / Asmalini Che Abu Shafie - Che Abu Shafie, Asmalini (2012)
There is a lack of research on leisure constraints and the types of leisure opportunities for Muslim when participating in leisure and recreational activities. Therefore, the present study explores the participation of Muslim in the available leisure and recreational opportunities in Kuching, Sarawak. The purposes of the present study were: a) to examine Muslim community with particular reference to leisure and recreational activity and b) to study their views of their leisure and recreation opportunities and constraints. The participants were 20 Muslim in Kuching, who agreed to be interviewed for the study. A qualitative face to face interview approach was used for the study. Results revealed that: a) respondents took advantage of the leisure and recreation opportunities provided by the Kuching City Council; b) constraints and barriers were not the limiting factors in respondents' use of provided facilities such as national parks, swimming pools and recreation centres, in part because of the flexibility of interpretation of the requirements of Islam. As a conclusion, respondents took advantage of the leisure and recreation opportunities provided by the Kuching City Council and constraints and barriers were not the limiting factors for them to use all the facilities provided.